PRINCIPLES OF LEADERSHIP 4.0 AND THE FORMATION OF INNOVATIVE LEADERSHIP COMPETENCIES IN CORPORATE GOVERNANCE - Allayor Rashidovich Ismailov (Scholar Express Journal, 2025)
This article analyzes the issues of forming innovative leadership competencies in corporate governance through the implementation of Leadership 4.0 principles. The study examines how digital technologies of the Industry 4.0 era (artificial intelligence, big data, blockchain) and methods of managing intellectual capital influence corporate governance processes. The authors provide a scientifically grounded explanation of mechanisms for developing innovative thinking, the ability to manage strategic change, and adaptive and transformational leadership skills within corporate governance
Keywords: Leadership 4.0; innovative leadership; corporate governance